Creditor Rights and Debt Allocation within Multinationals - Basak Akbel; Monika Schnitzer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
We analyze the optimal debt structure of multinational corporations choosing between centralized or decentralized borrowing. We identify how this choice is affected by creditor rights and bankruptcy costs, taking into account managerial incentives and coinsurance considerations. We find that partially centralized borrowing structures are optimal with either weak or strong creditor rights. For intermediate levels of creditor rights fully decentralized (centralized) borrowing structures are optimal if managers have strong (weak) empire building dencies. Decentralized borrowing is more attractive for companies focussing on short-term profitability. Credits are rather taken in countries with better creditor rights and more efficient insolvency systems.
urn:nbn:de:bvb:19-epub-13250-8
Keywords: G32; F23; 330; Multinational corporations; capital structure; creditor rights; coinsurance; internal capital markets; Multinationales Unternehmen; Kapitalstruktur; Schulden; Gläubigerschutz; Kapitalmarktrecht; Theorie